Diagnosing the vertical structure of the eddy diffusivity in real and idealized atmospheres. (19th June 2014) - Jansen, Malte; Ferrari, Raffaele
Abstract The Earth's extratropical troposphere is equilibrated by turbulent eddy fluxes of potential temperature and momentum. The equilibrated state has the remarkable characteristic that isentropic slopes leaving the surface in the subtropics reach the tropopause near the Poles. It has been speculated that turbulent eddy fluxes maintain this state for a wide range of radiative forcing and planetary parameters. In a previous study, the authors showed that this state needs to be associated with an eddy diffusivity of Ertel potential vorticity that is largest at the surface and decays through the troposphere to approximately zero at the tropopause. This result is confirmed in this study using atmospheric reanalysis and idealized numerical simulations. However, it is also shown that the vertical profile of the eddy diffusivity can change, resulting in different isentropic slopes and climates. This is illustrated with a series of idealized numerical simulations with varying planetary scales and rotation rates.